Classroom ethnography: Adapt or adopt? - Amnah Abdullah; Mohd. Zaki Ishak; Robert Francis Peters; Aisah Kasan (Global Academic Excellence, 2019)
Ethnography, in general, is a methodology that has been well known to many as conducted to study a culture-sharing group that could provide an understanding of a larger issue. However, ethnographic research in an educational setting is defined as research on and in educational institutions based on participant observation and/or permanent recordings of everyday life in naturally occurring settings. Then again, classroom ethnography who possess a family resemblance to ethnography is not well understood to many qualitative researchers in this region. Its value in the body of knowledge is not well understood also. In order to appreciate the value of this methodology, the history and development of this research with relation to science education could better enlighten the research community of its value and appropriateness in this region rich in its diverse culture and ethnicity. Different scholars have different scope and perspectives in understanding ethnography. The aim of this article is to open up new research directions in research methodologies for potential local postgraduates.